Interactions with youth justice and associated costs for young people with speech, language and communication needs. Issue 4 (27th May 2021) - Cronin, Paula; Addo, Rebecca
Abstract: Background: Individuals with speech, language and communication needs (SLCN) are at greater risk of contact with the criminal justice system. Diagnosis and appropriate treatment of SLCN reduces these risks, leading to better life outcomes for the individual as well as broader social and economic benefits. These youth represent a particularly high‐priority group for research into language deficits, as the juvenile justice system involves situations with a high risk or serious consequences that rely upon the application of effective language skills. Whilst some studies have established some gains in speech and communication from speech pathology (SP) interventions during custody, there is limited evidence on the long‐term impact of these gains following release from custody. Similarly, few studies have directly measured the cost savings associated with early SP on subsequent youth antisocial behaviour and crime. Aims: To estimate the youth antisocial behaviours, youth justice (YJ) contacts and associated costs (from a justice perspective) of childhood SLCN. Methods & Procedures: Using 12 years of data from a longitudinal study of Australian children and young people, we employ a panel fixed‐effects model to explore the relationship between SLCN and youth antisocial behaviour and youth offending between 12 and 17 years of age. Using these results, we estimate the cost of SLCN and subsequent cost savings associated with identification of SLCN. Outcomes & Results: The results showed that the annual cost of SLCN to the YJ system (exchange rate as at 9 December 2020) is A875 (95% confidence interval (CI) = A195, A1916) (US649, €536, £485) per person who participates in youth crime, which is due to higher rates of youth antisocial behaviour and youth offending. Identification of SLCN (defined by SP treatment) appears to have a positive impact on youth antisocial behaviour and crime, mediated through improved language and communication. On average, young people with a history of 'identified' SLCN incur A188 (95% CI = A42, A412) lower YJ costs (US140, €105, £115), compared with the same individual, before identification. Over the lifetime of the individual, this equates to A9.2 million (95% CI = A2.05 million, A20.2 million) (US6.8 million, €5.6 million, £5.1 million) cost savings to the YJ system (A3389 per person with SLCN) (2020 Australian dollars) (US2513, €2074, £1880). Conclusions & Implications: Overall, the findings revealed that young people with SLCN have an elevated risk of youth antisocial behaviour and crime. However, the identification of SLCN (and subsequent treatment) leads to changes in the offending risk trajectory for these individuals, resulting in lower rates of youth antisocial behaviour and consequently lower rates of crime and its associated justice costs. What this paper adds: What is already known on the subject: It is well documented in the literature that young people in contact with the justice system have much higher rates of previously undiagnosed SLCN than those of the general population. There is less known about whether the identification of SLCN (and subsequent treatment) leads to changes in the offending risk trajectory for these individuals, leading to lower rates of youth antisocial behaviours and crime. What this paper adds to existing knowledge: This study uses a longitudinal survey of 5000 children and young people to track the antisocial behaviour and crime‐risk trajectory of children and young people with SLCN. The study finds evidence that young people with 'identified' SLCN report less juvenile antisocial behaviour and lower YJ contacts after intervention. The potential lifetime cost savings associated with intervention is A9.2 million (95% CI = A2.05 million, A20.1 million) (US6.8 million, €5.6 million, £5.1 million). What are the potential or actual clinical implications of this work?: The findings of this study can quantify the effects (in terms of cost savings to the justice system) of the early identification and subsequent intervention for young people with SLCN.